Readers have shown a wide interest for QAS - Technical Centre for Agricultural and Rural Cooperation (Technical Centre for Agricultural and Rural Cooperation, 1986)
Ask us and we will answer Since its creation CTA has received many requests for information from individuals and organizations on a diverse range of subjects dealing with agriculture and rural development in ACP countries. Here are some examples:...